Investigation of Inflammation and Autophagy due to Biglycan-mediated TLR2/4 Signaling in Oral Lichen Planus Tissues. - GÜNİZİ, Özlem Ceren; GÜNİZİ, Hüseyin; ECİROĞLU, Hamiyet; YILDIZ, Fatma (Forbes Journal of Medicine, 2024)
Objective: Oral lichen planus (OLP) is a chronic oral mucosal disease of unknown etiology. Cellular immune response, basement membrane, and extracellular matrix (ECM) molecules are also noteworthy in the pathogenesis. We aimed to investigate the role of Biglycan (BGN) in Toll-like receptors (TLR)2/4- CD14 and TLR4-CD44 mediated signaling mechanisms in the pathogenesis of OLP. Methods: Twenty-one patients with a previous diagnosis of OLP and 21 patients with normal oral mucosa were included. RNA was isolated from biopsy samples of patients, and the gene expression of BGN, TLR2, TLR4, CD14, and CD44 was analyzed by quantitative real-time polymerase chain reaction and immunohistochemistry. Results: According to our findings, the fold change rates of BGN, TLR2, TLR4, and CD14 mRNA levels in tissues obtained from patients with OLP were higher compared with the control group. TLR2, TLR4, and CD14 fold change rates were statistically significant (p<0.05). CD44 co-receptor mRNA levels were higher in the control group (p<0.05). Similar results were obtained by immunohistochemical analysis. Conclusion: BGN expression has a pro-inflammatory effect in various disease models. The BGN levels in the tissues of patients with OLP were higher than those of the control group, but the difference was not statistically significant. However, TLR2/4-CD14 and CD44 levels were upregulated, as well as CD44 levels were downregulated. We suggest that inflammation signaling is activated and autophagy is inhibited in OLP. BGN-dependent inflammation and autophagy signaling in OLP are evaluated for the first time.